2018
DOI: 10.1051/epjconf/201817507002
|View full text |Cite
|
Sign up to set email alerts
|

Dual simulation of the massless lattice Schwinger model with topological term and non-zero chemical potential

Abstract: We discuss simulation strategies for the massless lattice Schwinger model with a topological term and finite chemical potential. The simulation is done in a dual representation where the complex action problem is solved and the partition function is a sum over fermion loops, fermion dimers and plaquette-occupation numbers. We explore strategies to update the fermion loops coupled to the gauge degrees of freedom and check our results with conventional simulations (without topological term and at zero chemical p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…This additional constraint makes the system much more stiff in a Monte Carlo simulation and the insertion of additional winding loops, i.e., additional charges is rare. This has, e.g., been observed in the simulation [29][30][31] of the worldline form [32] of the massless Schwinger model. It was found that in the grand canonical worldline simulation in particular the particle number suffers from very long autocorrelation times.…”
Section: Canonical Worldline Simulationssupporting
confidence: 55%
“…This additional constraint makes the system much more stiff in a Monte Carlo simulation and the insertion of additional winding loops, i.e., additional charges is rare. This has, e.g., been observed in the simulation [29][30][31] of the worldline form [32] of the massless Schwinger model. It was found that in the grand canonical worldline simulation in particular the particle number suffers from very long autocorrelation times.…”
Section: Canonical Worldline Simulationssupporting
confidence: 55%